ANTECEDENT OF COMMUNITY TRUST AND ITS IMPACT ON PARTICIPATION IN CONSTRUCTION SERVICES EDUCATION - Candra, Angga Asfan; Supriyono, Bambang; Hidayati, Firda (Erudio Journal of Educational Innovation, 2025)
Trust is a key element in the relationship between the government and the community, affecting the level of participation and involvement of the community in various programs and policies. This is known as the deliberative process, an approach to public policy that many experts believe can lead to successful public policy outcomes. The key to the deliberative process is public participation in government policy making and implementation, which should lead to high-quality democracy. This deliberative policy is formulated based on the results of joint decisions between the government and citizens through prior discussions. This deliberative process aligns with the mandate contained in the work copyright law, which encourages strengthening the role of the construction services community as a driver of construction services development. It mandates the government's authority to include the construction services community. This study aims to examine (1) the effect of government performance on public participation in construction services, (2) the effect of government performance on public trust in construction services, (3) the effect of public trust in construction services on public participation in construction services, and (4) the mediating role of public trust in construction services between government performance and public participation in construction services.The research approach used is a quantitative approach, specifically explanatory research. The research was conducted purposively at the Public Works, Spatial Planning, Housing, and Settlement Areas Office of North Kalimantan Province. The population of this study is the construction service community, represented in the construction service forum, which consists of various elements of the community. A saturated sampling method was employed. Data were analyzed using Structural Equation Modeling (SEM) techniques with Partial Least Squares (PLS) The results showed that all tested variables had a significant effect. Perceptions of government performance have a positive and significant effect on the participation of the construction service community in construction service guidance activities. Perceptions of government performance have a positive and significant effect on public trust in construction services. Trust within the construction services community has a positive and significant effect on community participation in construction services. Additionally, trust within the construction services community significantly mediates the relationship between perceptions of government performance and community participation in construction services. Based on these findings, it is recommended that the government effectively capture the expectations of the construction service community through regular satisfaction surveys, consider criticism and suggestions, and follow up on survey results, criticisms, and suggestions to improve performance and enhance trust within the construction service community.